Pengembangan Video Pembelajaran 3S untuk Mendongkrak Self Efficacy Siswa dalamMengambil Keputusan Studi Lanjut di Era Revolusi Industri 4.0 - Yang Gustida Aditya Jakti (Jurnal Didaktika Pendidikan Dasar, 2020)
The tricky problem in realizing national education goals in the era of the industrial revolution 4.0 related to specialization in junior high is the low self-efficacy of students in making further study decisions. The problem is related to the challenges of development and future goals of students. Based on experience during teaching, observation, and question and answer with 9th grade students, accepting students answer doubts in determining secondary school. Students take friends or pursue achievements without seeing their condition. This Innovative work is about video learning 3S (school, senior, support) which become a real solution to address the conflicts that occur in 9th grade students associated with low self-efficacy in making further study decisions. The development of this innovative work is of Research and Development (R&D) type by applying the ADDIE model. The 3S instructional video media (school, seniors, support) applied to 92 students in learning activities resulted in several studies. Based on data analysis, self efficacy and the ability to make decisions further increase heterogeneity. The percentage increase in self-efficacy increased varied, class 9F showed an increase of 5%, class 9G only increased by 1% and class 9I increased by 5%. The percentage of decision making towards further improvement, class 9F increased by 1%, class 9G increased by 2%, and class 9I only increased by 0.5%. However, students show high enthusiasm, are more serious and focused throughout the learning process. Students receive information as well as understanding more related to advanced studios after seeing 3S learning videos (school, seniors, support). Based on the data that has been obtained, it can be concluded that the 3S learning video (school, senior, support) is able to boost students' self efficacy in making further study decisions.